2003
DOI: 10.1103/physrevd.67.063521
|View full text |Cite
|
Sign up to set email alerts
|

Model independent approach to the dark energy equation of state

Abstract: The consensus of opinion in cosmology is that the Universe is currently undergoing a period of accelerated expansion. With current and proposed high precision experiments it offers the hope of being able to discriminate between the two competing models that are being suggested to explain the observations, namely a cosmological constant or a time dependent ''quintessence'' model. The latter suffers from a plethora of scalar field potentials all leading to similar late time behavior of the universe and, hence, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
177
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(184 citation statements)
references
References 52 publications
7
177
0
Order By: Relevance
“…Our task has been made easier by the availability of parametrizations which accurately describe the dynamics of the different quintessence models (Corasaniti & Copeland, 2003;Linder & Huterer, 2005). This allows In this thesis we have taken into account three levels of modification from a ΛCDM cosmology which are necessary if we wish to faithfully incorporate the effects of quintessence dark energy into a N-body simulation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our task has been made easier by the availability of parametrizations which accurately describe the dynamics of the different quintessence models (Corasaniti & Copeland, 2003;Linder & Huterer, 2005). This allows In this thesis we have taken into account three levels of modification from a ΛCDM cosmology which are necessary if we wish to faithfully incorporate the effects of quintessence dark energy into a N-body simulation.…”
Section: Discussionmentioning
confidence: 99%
“…The equation for w valid after matter-radiation equality is Copeland (2003) showed that this four parameter fit gives an excellent match to the exact equation of state. Table 3.1 gives the best fit values for the equation of state parameters for the different quintessence models taken from Corasaniti & Copeland (2003), with the addition of the INV2 model. The parametrization for the dark energy equation of state is plotted in Fig.…”
Section: Parametrization Of Wmentioning
confidence: 99%
See 2 more Smart Citations
“…A combined large scale structure (LSS), SNe, and CMB analysis has set an upper limit on Q-models with a constant w φ < −0.7 [4], and a more recent analysis of CMB observations gives w φ = −0.82 +0.14 −0.11 [5]. Furthermore, the SNe data and measurements of the position of the acoustic peaks in the CMB anisotropy spectrum have been used to put a constraint on the present w 0 φ ≤ −0.96 [6].The apparent brightness of the farthest SN observed to date, SN1997ff at redshift z ∼ 1.7, is consistent with that expected in the decelerating phase of the flat ΛCDM model with Ω Λ ≃ 0.7 [7], inferring w φ = −1 for z < 1.7. In addition, several attempts have been made to test different Q-models [8].…”
mentioning
confidence: 99%